Microeconomics - Pindyck, Robert S. (Pearson, 2015)
For undergraduate and graduate economics majors who are enrolled in an Intermediate Microeconomics course. A book that provides a treatment of microeconomic theory that stresses the relevance and application to managerial and public policy decision making. This edition includes a number of new topics, updated examples, and improved exposition of existing materials. For a complete multimedia book tour of Pindyck, Microeconomics, 8e, Click Here MyEconLab is an online homework, tutorial, and assessment product designed to personalize learning and improve results. With a wide range of int.